The Effects of Environmental Knowledge, Environmental Concern, and Green Brand Image on Green Purchase Intention with Perceived Product Price and Quality as the Moderating Variable. Issue 1 (March 2020) - Qomariah, A; Prabawani, B
Abstract: In recent years, public awareness and concern of green products have begun to increase. People are starting to pay attention to the ingredients in all the products they use. This condition triggers companies to create beauty products that are environmentally friendly and safe to use. This study aims to determine and explain the effects of environmental knowledge, environmental concern, the green brand image on green purchase intention with perceived product price & quality as a moderating variable. The type of this research is explanatory research with a quantitative approach. The sample used was 100 visitors of The Face Shop at Ciputra Mall Semarang. The sampling technique used was purposive sampling and accidental sampling. Data collection methods used were physical questionnaires and online questionnaires. Data processing using SmartPLS 3.2.8. The results of this study indicate that green brand image and the perceived product price & quality significantly influence the green purchase intention. While environmental knowledge and environmental concern do not significantly influence green purchase intention. The moderation type of perceived product price & quality of environmental knowledge is a quasi-moderator. Whereas the moderating type of variable perceived product price & quality towards environmental concern variables and green brand image is an antecedent.